Long-term Outcomes of Fibrin Glue–Assisted Intrascleral Haptic Fixation of Posterior Chamber Intraocular Lenses in Children. Issue 1 (January 2022) - Sinha, Rajesh; Asif, Mohamed Ibrahime; Kalra, Nidhi; Bansal, Mayank; Chauhan, Divya; Shekhar, Himanshu; Sharma, Namrata; Titiyal, Jeewan S.
Abstract : Objectives: To evaluate the long-term outcomes of intrascleral haptic fixation of posterior chamber intraocular lens (PCIOL) with fibrin glue in children. Methods: This is a retrospective case study conducted in a tertiary eye institute in North India. A total of 118 eyes of 82 children who underwent glued intrascleral haptic fixation of PCIOLs were retrospectively analyzed. Detailed analysis of the indication for surgery and ocular and systemic associations was performed. The outcome measures included intraoperative complications, final visual and refractive outcomes, and postoperative complications. Results: The mean age of the patients was 10.16±3.94 years. Fifty-one patients (62.2%) were male and 31 (37.8%) were female. The mean follow-up period was 31.28±13.22 months. The mean preoperative corrected distance visual acuity was 1.18±0.63 Logarithm of Mean angle of resolution (logMAR) which improved to 0.60±0.58 logMAR postoperatively at 6 weeks ( P <0.001). The mean preoperative and 6 weeks postoperative endothelial cell density were 3, 176.08±318.6 and 2, 936±289.9 cells/mm 2, respectively ( P =0.23). In the immediate postoperative period, corneal edema (19 eyes; 16.1%), decentered IOL/tilt (3 eyes; 2.54%), vitreous hemorrhage (3 eyes; 2.54%), optic capture (4 eyes; 3.38%), and hypotony (2 eyes; 1.69%) were seen. In the late postoperative period (>6 weeks), retinal detachment was observed in two eyes that had associated Marfan syndrome. Cystoid macular edema was seen in four eyes (3.38%), and glaucoma was seen in five eyes (4.23%). Conclusions: Fibrin glue–assisted intrascleral haptic fixation of a PCIOL is a safe and effective method to manage aphakia with inadequate capsular support in children. Abstract : Supplemental Digital Content is Available in the Text.